The development and validation of the Treatment of Autoimmune Bullous Disease Quality of Life questionnaire, a tool to measure the quality of life impacts of treatments used in patients with autoimmune blistering disease. (31st October 2013) - Tjokrowidjaja, A.; Daniel, B.S.; Frew, J.W.; Sebaratnam, D.F.; Hanna, A.M.; Chee, S.; Dermawan, A.; Wang, C.Q.; Lim, C.; Venugopal, S.S.; Rhodes, L.M.; Welsh, B.; et al.
Summary: Background: Treatments for autoimmune blistering diseases have significant risk of medical complications and quality of life impacts during treatment, and it is difficult to differentiate these impacts from disease burden or the effects of treatment. Objectives: To develop a quality of life instrument specific to the effects of treatments used in patients with autoimmune bullous disease (AIBD). Methods: A comprehensive item generation process was used to build a 45‐item pilot Autoimmune Bullous Disease Quality of Life (ABQOL) questionnaire, distributed to 70 patients with AIBD. Experts in bullous disease refined the pilot ABQOL, selecting only those questions pertaining to the treatment effects. This pilot Treatment of Autoimmune Bullous Disease Quality of Life (TABQOL) questionnaire was administered to 70 patients, before factor analysis was performed to yield the final questionnaire of 17 questions. Validity and reliability were evaluated across a range of indices. Results: Face and content validity were established through a comprehensive patient interview process, expert review and summaries of treatments used. The questionnaire was found to have appropriate correlation with the Dermatology Life Quality Index ( r  =   0·64) and the level of treatments used ( P  <   0·01), and was found to be responsive to overall variations in treatment burden. The TABQOL was also found to be a reliable instrument as evaluated by internal consistency (Cronbach α = 0·892) and test–retest reliability ( r  =   0·99). Conclusions: We have shown that the TABQOL questionnaire is a valid and reliable instrument that may to be used to measure treatment burden in AIBD and serve as an end point in clinical trials. Abstract : What's already known about this topic? Treatments for autoimmune bullous disease (AIBD) have a significant risk of medical complications and quality of life impacts during treatment. It is difficult to differentiate quality of life impacts from disease burden or the effects of treatment. What does this study add? The Treatment of Autoimmune Bullous Disease Quality of Life questionnaire allows quantitative measurement of treatment‐based quality of life impacts in AIBDs. Longitudinal measurements allow consideration of optimal balance between disease control and treatment burden.